Multifaceted mechanisms regulating Brassica oleracea growth under shading gradients in an agrivoltaic system: Integrated responses of the soil-plant system and transcriptomic analysis - Chen, zhuo; Liu, Xiaocui; Ban, Tiantian; Ma, Chao (International Journal of Agricultural and Biological Engineering, 2026)
Agrivoltaic systems represent a sustainable land-use paradigm capable of synergistically generating electricity and producing agricultural crops on the same piece of land. However, the mechanisms by which photovoltaic shading affects crop growth are not fully understood. This study investigated these mechanisms using Brassica oleracea as a model plant at an agrivoltaic base in Guizhou Province, China. Treatments included high shading (HP, 70%-80%), low shading (LP, 20%-30%), and no shading (NP). This study systematically examined the regulatory effects of these shading gradients on soil physicochemical properties, plant growth physiology, and transcriptomic expression. Results indicated that the NP treatment yielded the highest B. oleracea biomass, while the LP treatment significantly enhanced the content of quality components such as sugars and starch while maintaining a relatively high yield. The HP treatment promoted the accumulation of structural substances (cellulose, lignin) and maintained higher soil nutrient levels. Transcriptome analysis revealed that shading significantly altered pathways involved in photosynthesis, starch and sucrose metabolism, and plant hormone signal transduction. Several key responsive genes were identified, including Bo4g182560 (a chlorophyll a/b-binding protein) and Bo3g039200 (involved in jasmonic acid biosynthesis). Furthermore, different shading environments induced distinct antioxidant strategies: the NP zone relied on peroxidase (POD) activity to manage oxidative pressure associated with full sunlight exposure, whereas the HP zone maintained redox homeostasis by enhancing catalase (CAT) activity. By integrating multi-omics data spanning soil, plant, and molecular levels, this study partially elucidates the adaptive regulatory network of B. oleracea in the agrivoltaic system, specifically involving photosynthesis, starch and sucrose metabolism, plant hormone signal transduction, and distinct antioxidant strategies, providing a theoretical basis and genetic resources for system optimization and precise crop configuration. Key words: agrivoltaic system; shading gradient; Brassica oleracea; soil physicochemical properties; crop physiology; transcriptomics DOI: 10.25165/j.ijabe.20261904.10486 Citation: Chen Z, Liu X C, Ban T T, Ma C. Multifaceted mechanisms regulating Brassica oleracea growth under shadinggradients in an agrivoltaic system: Integrated responses of the soil-plant system and transcriptomic analysis. Int J Agric & BiolEng, 2026; 19(4): 152–164.